2003
DOI: 10.1021/es0200645
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Response of Soils and Vegetation to Heavy Metal PollutionA Case Study

Abstract: Fast and cost-effective detection of industrial pollution can significantly promote its ecological, economic, and social assessment. A magnetometric method, used for qualitative determination of anthropogenic contamination, meets these requirements but needs further development in more quantitative terms. It could be used successfully in numerous cases when the heavy metals coexist with strongly magnetic iron oxide particles in the source dust. We present an integrated magnetic and geochemical study that exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(40 citation statements)
references
References 27 publications
0
35
0
2
Order By: Relevance
“…Magnetic mapping in magnetism has been well accepted for investigating industrial and urban pollution in different environments, such as soils, rivers/streams and lakes, different vegetative habitats, and roads (e.g., Hunt et al, 1984;Hoffmann et al, 1999;Matzka and Maher, 1999;Petrovský and Ellwood, 1999;Jordanova et al, 2003;Amereih et al, 2005;Lu et al, 2005;Zhang et al, 2006;Kim et al, 2007;Chaparro et al, 2007;Maher et al, 2008). A considerable number of studies have indicated relationships between magnetic parameters and heavy metal concentrations based on a genetic relationship from simultaneous production of both particle sources (e.g., Beckwith et al, 1986;Georgeaud et al, 1997;Petrovský et al, 1998;Knab et al, 2001;Spiteri et al, 2005;Chaparro et al, 2006Chaparro et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic mapping in magnetism has been well accepted for investigating industrial and urban pollution in different environments, such as soils, rivers/streams and lakes, different vegetative habitats, and roads (e.g., Hunt et al, 1984;Hoffmann et al, 1999;Matzka and Maher, 1999;Petrovský and Ellwood, 1999;Jordanova et al, 2003;Amereih et al, 2005;Lu et al, 2005;Zhang et al, 2006;Kim et al, 2007;Chaparro et al, 2007;Maher et al, 2008). A considerable number of studies have indicated relationships between magnetic parameters and heavy metal concentrations based on a genetic relationship from simultaneous production of both particle sources (e.g., Beckwith et al, 1986;Georgeaud et al, 1997;Petrovský et al, 1998;Knab et al, 2001;Spiteri et al, 2005;Chaparro et al, 2006Chaparro et al, , 2008.…”
Section: Introductionmentioning
confidence: 99%
“…In several studies, a significant correlation between magnetic susceptibility and heavy metal content in soils was found (e.g., Heller et al 1998;Dearing et al 2001;Lecoanet et al 2001;Hanesch et al 2003;Jordanova et al 2003). It has been well established that aerosols from varieties of industrial combustion processes possess a significant mineral magnetic component (Hunt et al 1984;Beckwith et al 1986), and that these minerals make significant contribution to the magnetic component of topsoil horizons, especially in urban areas and sites downwind of industrial centers .…”
Section: Introductionmentioning
confidence: 99%
“…Another possible source of magnetic property in vegetation is due to the deposition of atmospheric dust particles of different origins on plant leafs. Dust itself contains strongly magnetic iron oxide particles (Hunt et al 1984) and could be a reason for enhanced magnetic properties of vegetation (Matzka and Maher 1999;Jordanova et al 2003). At this point, it has to be noted that dry Tendu leaf is collected from forests and used to role the tobacco sample (U1) to prepare bidi.…”
Section: Magnetic Measurementsmentioning
confidence: 99%